(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This article presents the clinical features, imaging findings, treatment methods, and outcomes of five cases of fibrous dysplasia, along with a literature review to emphasize the importance of accurate diagnosis and appropriate management. Methods: A case series of five patients diagnosed with fibrous dysplasia at Hospital for Traumatology and Orthopaedics at Ho Chi Minh city is described. Data collected include clinical presentation, imaging, treatment, and postoperative follow-up. A literature review was also conducted using updated sources. Results: Among the 5 cases, 3 patients had monostotic fibrous dysplasia, 1 had polyostotic fibrous dysplasia, and 1 was diagnosed with McCune-Albright syndrome. 4 patients underwent surgery due to pathological fractures, and 1 patient was treated for bone deformity and persistent pain. Surgical treatments included locking plate fixation and intramedullary nailing. Overall, treatment outcomes were favorable with no major complications. Conclusion: Fibrous dysplasia presents with diverse manifestations and requires individualized treatment. Surgery is indicated in symptomatic cases, and long-term follow-up plays a crucial role.